Efficacy of Tumor Necrosis Factor Inhibitors in Patients With Ankylosing Spondylitis - Deniz DÜLGEROĞLU ERDOĞDU; Ajda BAL; Özgür KARAAHMET; Sibel ERKOÇ; Tuğba YALÇIN; Aytül ÇAKCI (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate the efficacy of tumor necrosis factor-alpha blockers such as infliximab, etanercept, and adalimumab in the treatment of ankylosing spondylitis. Patients and methods: The outcome of tumor necrosis factor-alpha blocker treatment was analyzed retrospectively in 59 patients with ankylosing spondylitis who were being treated in our clinic during last nine years. The patients’ Assessment of SpondyloArthritis International Society (ASAS) 20 and ASAS 40 response rates, adverse drugs effects, and treatment compliance were evaluated. Results: ASAS 20 response was achieved by 89.8% of the patients in the third month, and by 93.2% in the sixth month. ASAS 40 response was achieved by 61% of the patients in the third and sixth month. No statistically significant difference was detected between the three tumor necrosis factor-alpha blockers with regards to the ASAS 40 response rates. Mild infections, observed in 31 of the patients, were the most common side effects. Serious side effect was observed in only one patient. The number of patients who withdrew from the treatment for various reasons was six. Conclusion: Treatment with infliximab, etanercept, or adalimumab is clinically effective and safe.